DEVELOPMENT OF PHYSICS IDENTITY RESEARCH IN THE LAST DECADE (2014-2024): A BIBLIOMETRIC ANALYSIS - Wicaksono, Bayu Aji; Kurniawan, Aris; Kuswanto, Heru (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
Physics identity plays a significant role in shaping individuals’ careers and academic engagement in physics. This study aims to analyze the development of research on physics identity over the past decade using bibliometric analysis based on Scopus data. A total of 114 documents were collected, then filtered based on publication year (2014–2024), English language, and article type, resulting in 60 articles for analysis. This study examines publication trends, geographical distribution, and under-researched topics in physics identity. Using VOSviewer and Publish or Perish 8 software, the findings indicate a fluctuating increase in publications, with a predominant focus on gender issues and identity-forming factors such as self-efficacy, recognition, and motivation. However, the research of physics identity concentrated in the United States, highlighting a lack of studies in other regions. Additionally, efforts to address the physics identity crisis are still minimal. This study provides a comprehensive synthesis of the field and highlights the need for further research on alternative strategies to mitigate gender stereotypes and enhance physics identity, particularly in countries with low research contributions.